PENGARUH FAKTOR PREFERENSI BERMUKIM MASYARAKAT DALAM MEMILIH HUNIAN PERUMAHAN TERHADAP KONDISI FISIK LINGKUNGAN DI PINGGIRAN SELATAN KOTA SURAKARTA - Erlana Citra Putri Kharisma; Galing Yudana; Winny Astuti (ARSITEKTURA, 2017)
Abstract: Limited land for housing in Surakarta eventually make the society chosen an alternative to living in residential housing on the southern fringe of Surakarta.The problems in this research is how influence of factors society living preference when choosing a residential housing to the physical condition of the environment on the southern fringe of Surakarta. The purpose of research is to find the influence of factors society living preference when choosing a residential housing to the physical condition of the environment on the southern fringe of Surakarta. The used research method was quantitative with deductive approach. The analysis technique used is descriptive eksplanatif analysis. Overall the conclusion of this research is factors society living preference when choosing a residential housing give high influence to physical condition of the environment on the southern fringe of Surakarta. When viewed its influence to each of these aspect physical condition of the environment, factors society living preference when choosing a residential housing give high level of influence on the residential density condition, give high level of influence on the facilities condition, give high level of influence on the infrastructure condition and give medium level of influence on the accessibility condition. Keyword: Housing, Living preference, Physical condition of the environment